Efeito do Programa de exercícios físicos em contexto domiciliar em idosos com doença de Alzheimer (AD-HOMEX) na força muscular, na mobilidade funcional e na funcionalidade: um ensaio clínico controlado e randomizado - Cezar, Natália Oiring de Castro (2021)
Background: Physical exercise in the home environment may be an important non-pharmacological intervention strategy for the older people with Alzheimer's disease (AD), due to their greater adherence and ease for the caregiver. Few studies have analyzed the implications of this type of intervention on muscle strength, functional mobility and functionality. Aims: To verify the effect of the home-based physical exercise program for older people with Alzheimer's disease (AD-HOMEX) in older people with AD on muscle strength, functional mobility and functionality. Method: This is a clinical trial with 40 older people from the community with AD in mild and moderate phases, randomized into Intervention Group (IG) and Control Group (CG). The IG performed exercises, aimed at functionality, muscle strength, balance, cognitive, aerobic endurance, and motor dual task at home for 16 weeks, three times a week. The CG did not perform any intervention. The clinical trial followed the recommendations of CONSORT and SPIRIT. Participants were evaluated by blind examiners regarding the allocation of the groups, initially (M1) and after 16 weeks (M2). The evaluation consisted of anamnesis, muscle strength measurements (isokinetic and manual dynamometer, sit and stand test 5 times (5XSTS) and 30 seconds), functional mobility (Timed Up and Go) and functionality (Direct Assessment of Functional Status and Activities of Daily Living Questionnaire-ADL-Q). The multivariate analysis of variance tested the interaction between groups (intervention and control) and moments (M1 and M2). A significance level of α=0.05 was adopted. Results: 40 and 35 participants were evaluated in moment 1 and moment 2, respectively. Four participants from the IG and one participant from the CG were lost. There was high adherence to training (80%) and sessions (93.75%). There was a significant interaction between group and moment for 5XSTS (p = 0.011) and for ADL-Q (p = 0.001). The GI improved the performance between moments by the 5XSTS (p = 0.020) and by the ADL-Q (p = 0.006) and showed a reduction in the risk of falls (p = 0.00) and in the severity of the functional impairment (p = 0.005), while the CG worsened both (p = 0.006; p = 0.010), respectively. Conclusions: These results suggest that the AD-HOMEX significantly increased muscle strength and functionality, in addition to decreasing the risk of falls. The home-based protocol favored good adherence and adherence, since it does not require commuting, enabling better cost-benefit for these older people, their caregivers and therapists. AD-HOMEX contributes to advances in the area of scientific research on this population and the protocol serves as a theoretical foundation for the development of measures for clinical interventions and health promotion, in order to prevent debilitating complications resulting from the disease. Therefore it can be a guide for clinical professionals in the development of effective intervention strategies with physical exercise that neutralize adverse outcomes and maximize the clinical course of the disease.